The Accounting Profession during COVID-19 Pandemic A Study on the Corona Pandemic Effect on Audit Quality: Perceptions of Iraqi Accounting Auditors - Sura Naufel Bahjat; Salih Yahya Saleh (Journal of Madenat Alelem University College, 2021)
The primary purpose of this research is to study the effect Corona-Virus Pandemic (CVP) on quality of auditing reports and auditors from the point of view of Iraqi auditors. A quantitative research method had been adopted through a questionnaire form to achieve its aims. Auditors were asked to state their opinions regarding audit quality statements based on a five-point Likert scale. An electronic questionnaire link was distributed due to the current pandemic instead of a regular (paper-based) form, 200 questionnaires were received, of which 89 answers were valid for analysis. Our research examined some important findings, the most important of which is that CVP surely has a noteworthy effect on audit quality based on the research sample’s opinions.